CR spray - Syed Osman, Syarifah Norziana; Azhar, Muhammad Ilham Husaini; Saharuddin, Futra Ramadani; Ahmad Rafie, Irdina Maisarah; Rosdy, Nur Athirah (Universiti Teknologi MARA, Kedah, 2023)
Nowadays, people always use different kinds of cleaning products to clean and repel. Which is that itcontains a huge amount of chemicals. Those people do not know how dangerous these products are for them and the environment. Based on this issue, we are planning to produce cleaning and repellent sprays. We chose lemon as the main ingredient in our product because it contains citric acid and phytic acid. Therefore, it is good for cleaning and removing grease. The ingredients used in the product are lemon peel, lemongrass, and vinegar. Firstly, we check and choose the best quality of lemon peel and lemongrass. After that, we soak them in vinegar and put them in an airtight container. The next step is filtering them. Lastly, bottling and labelling We have given our product a test, and it has been proven that our product does not pose any potential harm to people.